Diversity of Ants (Hymenoptera: Formicidae) in a Sub-Montane and Sub-Tropical Cityscape of Northeastern Mexico - García-Martínez, Miguel Angel; Vanoye-Eligio, Venancio; Leyva-Ovalle, Otto Raul; Zetina-Córdoba, Pedro; Aguilar-Méndez, Mario Josué; Mejía, Madai Rosas (Sociobiology, 2019)
ABSTRACT - The role of urban ecosystems in maintaining biodiversity and ecosystem services is highly variable because of the heterogeneity of habitats in human-use landscapes. We analyzed ant diversity in a sub-montane and sub-tropical urban area of northeastern Mexico to determine the conservation value of this cityscape. Ants were collected in 16 across the cityscape, including spaces at the periphery and urban center, during the rainy season (August to October) of 2015. To capture ants, eight trap traps were installed along a 100-m transect, and hand collections were performed. In total, 7,415 ant workers belonging to 32 species, 23 genera, 11 tribes, and 5 sub-families were collected. The richness and structure of the assemblages varied among the sampling sites. The compositional similarity also varied significantly among sampling sites, and unique species were found in four sites. Each site showed an important and particular ant assemblage that differed from that of the other sites and the surrounding habitats in the cityscape. The results suggest that some sampling sites in the studied cityscape may contribute to the conservation of certain ant groups and invertebrate communities threatened by urban intensification. Ultimately, our findings support the importance of conserved areas and green spaces for the conservation of native species in and near urban areas.